2021
DOI: 10.1186/s11689-021-09379-w
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress indices in ASD children in Sub-Sahara Africa

Abstract: Background The pathogenesis of autism spectrum disorder (ASD) remains a medical challenge even in the developed world. Although genetics and epigenetic factors have been variously indicted as major causes of the disorder, development of oxidative stress especially in the formative years of children has equally gained prominence as an etiological basis of the disorder. Oxidative stress is characterized by the production of excessive amounts of free radicals, decreased levels of antioxidants with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
(27 reference statements)
1
11
0
Order By: Relevance
“…However, higher MDA and AOPP levels were observed in children with ASD in comparison with non-related control ( P = .0001), these results were similar to the results of Meguid et al, 18 Omotosho et al, 19 and Altun et al 20 studies, which found significantly higher levels of MDA in children with ASD when compared with control with no ASD ( P < .0001). Furthermore, our findings corresponded with the results of Ahmad et al study, 21 which found higher levels of AOPP (+120.6%) in children with autism spectrum disorder when compared with the control ( P ⩽ .05), denoting the relation between oxidative stress and ASD.…”
Section: Discussionsupporting
confidence: 87%
“…However, higher MDA and AOPP levels were observed in children with ASD in comparison with non-related control ( P = .0001), these results were similar to the results of Meguid et al, 18 Omotosho et al, 19 and Altun et al 20 studies, which found significantly higher levels of MDA in children with ASD when compared with control with no ASD ( P < .0001). Furthermore, our findings corresponded with the results of Ahmad et al study, 21 which found higher levels of AOPP (+120.6%) in children with autism spectrum disorder when compared with the control ( P ⩽ .05), denoting the relation between oxidative stress and ASD.…”
Section: Discussionsupporting
confidence: 87%
“…In the case of autism mitochondrial abnormality, augmented oxidative stress and decreased antioxidant capacity have been reported in autistic persons, all of which may be responsible for neuroinflammation and autism pathology [76,77]. Recent analysis of blood samples from children with autism spectrum disorders revealed reduced total plasma peroxidase and total antioxidant capacity, resulting in an imbalance in the oxidant/antioxidant ratio and abnormalities in neuronal transduction [78]. Zawadzka et al [79] showed that impaired brain development is a consequence of inflammatory processes inducing oxidative stress and mitochondrial damage, which in turn exacerbate oxidative stress, triggering further cellular damage.…”
Section: Neurodevelopmental Disordersmentioning
confidence: 99%
“…The characteristics of the studies included in the meta-analysis are shown in Table 1 . The meta-analysis of Pb levels in hair included 17 studies [ 19 , 32 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ], 13 studies in whole blood [ 20 , 31 , 34 , 44 , 58 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ], and 8 studies in urine [ 24 , 34 , 36 , 58 , 70 , 71 , 72 , 73 , 74 ].…”
Section: Resultsmentioning
confidence: 99%